Estudo de dosagens de misturas 100% RAP na fabricação de blocos para pavimentos intertravados - Flores, Guilherme Ceretta (2022)
In the process of restoring a highway, one of the biggest problems is the disposal of waste generated by milling the asphalt coating. On the other hand, the cost of asphalt pavements has risen more and more in recent years. Using milled material, also called RAP (Reclaimed Asphalt Pavement), in the composition of new pavements is a solution from an economic and environmental point of view. In addition to asphalt paving, another very widespread type is interlocking paving, especially with concrete blocks. This work aims to combine the use of RAP with the production of blocks for interlocking paving, using 100% RAP asphalt mixtures. For this, the study was divided into two stages. The first consisted of evaluating two RAPs and two rejuvenating agents (one for hot mixtures and the other for cold mixtures). The hot mixes were produced at the DoA temperature of the RAPs and the cold mix was produced within the additive manufacturer's recommendations. In this step, the samples were molded in the gyratory compactor and evaluated for compressive strength, tensile strength, resilience modulus and abrasion wear. In the second stage, two mixtures that obtained the best overall performance were molded as interlocking blocks measuring 20x10x8 cm and evaluated for compressive strength and abrasion wear. The results of the first stage showed that the mixtures recycled with RAP 50/70 obtained greater resistance to compression, traction and modulus of resilience, while they presented greater wear due to abrasion, indicating that they are more rigid and susceptible to damage due to fatigue, despite resisting better to traction and compression. Mixtures with RAP 60/85, on the other hand, tended towards lower rigidity, with lower compressive, tensile and MR resistance and greater resistance to wear by abrasion. Furthermore, the application of rejuvenating agents significantly reduced the stiffness of the RAPs. A greater drop in tensile and compressive strength was noted, as well as resilience modulus in the mixtures recycled with RAP 60/85. This indicates that the rejuvenating agent can alter some of the elastic properties of the polymers contained in the modified binder. Cold recycling did not obtain satisfactory rates to pass to the second stage, but the potential to use it as a base to replace BGS was noted. The hot recycled mixtures RAP 50/70 + Anova 1815 and RAP 60/85 100% stood out for presenting a better balance between their performances relative to RC, RT, MR and abrasion wear and were taken to the second stage of the research. The results of the second stage indicated that the blocks with RAP presented compressive strength between 16.34 and 18.26 MPa, not meeting the requirements of NBR 9781/2013, which requires at least 35 MPa. In wear by abrasion, the blocks showed mass loss between 10.94% and 18.66%, which are satisfactory rates. It was concluded that the evaluated blocks, despite not complying with NBR 9781, could be used on pedestrian-only roads, public sidewalks, bike paths, residential garages and exclusive roads for light vehicles, with low traffic.